Teenage birth leads to short stature and anemia: Evidence from a longitudinal study of 10,000 girls in India - Pant, Anjali; Scott, Samuel P.; Walia, Monika; Menon, Purnima; Nguyen, Phuong Hong (American Society for Nutrition, 2021)
Objectives: Home to one in five adolescents globally and a tradition of marrying young, India faces a huge challenge of teenage births. Early birth can be detrimental to the health and wellbeing of the teenage mother and her child, but few studies have followed teenage girls over time to understand these effects. We assessed the impact of early birth on female adolescents' undernutrition status. Methods: We used longitudinal data collected under a project called UDAYA that surveyed adolescent girls in northern India (Uttar Pradesh and Bihar) in 2015–16, with a follow-up round in 2018–19. Girls with no prior birth in round one were grouped as follows: still no birth in round two (reference group; n = 7,197), birth at age < 19 years by round two (early birth group; EB; n = 1,192), and birth at age > = 19 years by round two (later birth group; LB; n = 1,474). Using multivariate logistic and ordinary least square regression models, we examined whether EB or LB predicted height for age z-score (HAZ), stunting, BMI for age z-score (BMIZ), thinness, hemoglobin (Hb), and anemia. Models were controlled for cluster sampling design and individual and household characteristics. Results: The prevalence of undernutrition was higher in the EB group (stunting: 53%, thinness: 23%, anemia: 77%) and the LB group (stunting: 55%, thinness: 29%, anemia: 64%) compared to the reference group (stunting: 35%, thinness: 16%, anemia: 63%). The EB group was more likely to be short for their age (adjusted odds ratio (AOR): 1.30, 95% confidence interval (95%CI): 0.96,1.76), thin (AOR: 1.09, 95%CI: 0.68, 1.75), and anemic (AOR: 2.01, 95%CI: 1.39, 2.90) compared to the reference group. HAZ and Hb levels were on average 0.16 SD (95%CI: –0.30, –0.03) and 0.49 gm/DL (95%CI: –0.76, –0.22) lower, respectively, and BMIZ level was 0.22 SD (95%CI: 0.00, 0.43) higher for the EB group. Similar findings were observed for the LB group but were non-significant. The impact of EB on stunting and thinness was non-significant. Conclusions: In adolescent girls, early birth can contribute to stunting and anemia. initiatives to increase age at marriage and at birth would likely also benefit nutritional outcomes in adolescents.